THE USE OF K-MEANS ALGORITHM ON DATALOG HONEYNET FOR PROFILING DDOS ATTACKS - Winda Andrini Wulandari (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2017)
Cloud computing are admired for excellence, flexible benefits, and can be used together in various aspects and areas of business. According to Arbor Network that cloud technology is very vulnerable to DDoS attacks and the frequency of attacks has increased sharply in recent years.This research is the result of cooperation with AWN University and Indonesia Honeypot Project (IHP) Ministry of Communications and Informatics. The results suggest that honeynet as a way to protect and monitor the security of public cloud computing networks, and analyze its datalog through the k-means method approach to recognize cyber profilling DDoS attacks based on the timestamp recorded in the data.